Gender inclusiveness in student learning materials: Study of elementary school context in Indonesia - Salsabila, Indri; Hasanah, Anisa Rohmah; Mutakin, Hendriyan Ihsan; Lestari, Triana (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2024)
This study intends to evaluate the gender inclusivity in learning and education research field's growth trend from 2013 to 2023. The steps of the research are as follows: (i) assembling the tools and materials; (ii) organizing meetings; (iii) screening; (iv) visualizing; and (v) reviewing the data and outcomes that have been published. There were 988 articles in the keyword search results for "Gender," "Inclusiveness," "Learning materials," "Elementary School," and "Indonesia." A more equal and inclusive learning environment for all students can be achieved by include gender in student learning materials, according to the research findings. Students are more likely to feel appreciated and respected when they recognize themselves in the learning materials. Additionally, it supports and equalizes constructive gender roles and works to dispel harmful gender stereotypes.